Influence of Pectin as a green polymer electrolyte on the transport properties of Chitosan-Pectin membranes - Pasini Cabello, Sergio David (2017)
Novel blend membranes have been prepared from Chitosan (CH), Pectin (PEC) andtheir mixtures. The obtained samples were cross-linked and sulfonated beforecharacterization. The results show that CH/PEC membranes display structural changes on the chemical and physical properties as a function of composition. DSC analysis reveals an endothermic peak due to the scission of the ionic pairs between carboxylic groups and ammonium groups, which produces a strong change on physical properties such as methanol permeability and proton conductivity. The methanol permeability decreases with the amount of Pectin from (4.24±0.04)x10-6 cm2/s for pure Chitosan membrane to (1.51±0.03)x10-6 cm2/s for blend CH/PEC membranes when the amount of Pectin is 50% (v/v). The proton conductivities of the blend membranes follow a similar behavior. For a pure CH membrane the conductivity is 2.44x10-3 S/cm, decreasing with pectin content until the composition 50/50 (v/v), in which the conductivity drops almost one order of magnitude.